The cost of dying and what you can do about it - Arvio, Raymond Paavo (New York : Harper & Row Publishers, Inc., 1974)
This book is designed to provide encouragement, practical advice and guidance for nonprofit memorial societies, for religious organization, for consumer organizations and for consumers.
The Future of Death -- Change Is Not Easy -- It All Begins with a Memorial Society -- Looking Ahead: The Ideal Conversation with the Ideal Consumer -- First Steps Toward Consumer Ownership: The Board and the Membership -- The Working Philosophy of a Consumer-owned Facility -- The Day-to-Day Business -- Opening Day -- Variants for a Future Time.
Includes bibliographical references and index.
Keywords: UNDERTAKERS AND UNDERTAKING -- UNITED STATES